Clinical insights: Anxiety levels and sleep quality among Hang Tuah Faculty of Medicine's class of 2017-2022 pre-clinical and clinical Students - Ronald Pratama A.; Janette Alvina; Joel Timothy; Jihan Delima; Jocelyn Christabella; Kadek Aris Saputra Mulya; Hendra Widjajanto; Renata Prameswari; I Ketut Tirka Nandaka (Universitas Muhammadiyah Surabaya, 2024)
Anxiety is a global psychiatric phenomenon, while poor sleep quality remains a pressing public health issue. The arduous medical education journey exposes students to prolonged stress, potentially exacerbating anxiety and sleep disturbances. This study investigates the correlation between anxiety and sleep quality in Hang Tuah Faculty of Medicine students, bridging the pre-clinical and clinical phases. Employing an analytical observational approach with a cross-sectional design, this study enrolled students from pre-clinical (batches 2020, 2021, 2022) and clinical years (batches DM45, DM46, DM47). Among the 409 approached participants, 296 met the inclusion criteria after excluding 113 samples. Data collection utilized online questionnaires with acquired informed consent. Sleep quality was evaluated via the Pittsburgh Sleep Quality Index, generating scores from 0 to 21. This study showed significantly robust evidence of an association between anxiety and sleep quality (p-value: 0.0001; r: 0.342) across both pre-clinical and clinical students. This study underscores a direct relationship: elevated anxiety levels correspond to diminished sleep quality. Such findings resonate with the prevailing challenges in medical education and their impact on students' mental and physical well-being. Implementing targeted interventions is crucial to address these concerns. In conclusion, this study underscores the undeniable link between anxiety and sleep quality among Hang Tuah Faculty of Medicine students, encompassing the years 2017 to 2022. The implications are far-reaching, emphasizing the necessity of interventions that enhance both psychological well-being and sleep quality. By recognizing and addressing these challenges, medical institutions can foster healthier academic environments and better equip students for their medical careers.